2019
DOI: 10.1038/s41598-019-45402-w
|View full text |Cite
|
Sign up to set email alerts
|

PolyBall: A new adsorbent for the efficient removal of endotoxin from biopharmaceuticals

Abstract: The presence of endotoxin, also known as lipopolysaccharides (LPS), as a side product appears to be a major drawback for the production of certain biomolecules that are essential for research, pharmaceutical, and industrial applications. In the biotechnology industry, gram-negative bacteria ( e . g ., Escherichia coli ) are widely used to produce recombinant products such as proteins, plasmid DNAs and vaccines. These products are contaminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 92 publications
0
17
0
Order By: Relevance
“…PolyBalls were prepared using the emulsion/solvent evaporation technique. Briefly, 10 mg/mL of PCL solution in 10 mL of ethyl acetate was injected into 50 mL of 1% poly­(vinyl alcohol) (PVA) solution using a syringe pump ( K d Scientific) at a flow rate of 40 mL/h. The emulsions were homogenized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PolyBalls were prepared using the emulsion/solvent evaporation technique. Briefly, 10 mg/mL of PCL solution in 10 mL of ethyl acetate was injected into 50 mL of 1% poly­(vinyl alcohol) (PVA) solution using a syringe pump ( K d Scientific) at a flow rate of 40 mL/h. The emulsions were homogenized.…”
Section: Methodsmentioning
confidence: 99%
“…An opportunity to overcome the toxin contamination issue emerged from our recent findings of effective endotoxin removal through its interaction with and adsorption onto nanometer-sized poly-ε-caprolactone (PCL) nanoparticles (NPs) or PolyBalls. More specifically, when PolyBalls in powder form are mixed with an endotoxin aqueous solution, they were found to remove >99% of endotoxins from solutions. We hypothesize that PolyBalls have the potential to adsorb and remove both endotoxins and cyanotoxins from solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The coagulation conditions, cellulose type, and concentration control the film properties. [64] Additives, for example, metal and metal oxides, [65][66][67][68][69][70] activated carbon, [71] dyes, [72] or polymeric nanoparticles, [73] were employed to tailor, modify, or enhance film properties. Blending with additives is not always necessary to achieve better mechanical properties.…”
Section: Films and Membranesmentioning
confidence: 99%
“…Studies have reported that silver nanoscale particles also act as a binder to bond the carbon nanotubes together [74]. Silver nanoparticles (AgNPs) have been utilized to extract lipopolysaccharides (LPS) from a water mixture, which cause inflammatory reactions, resulting in tissue injury, with up to 97 percent effectiveness [75]. AgNPs can also diminish the regrowth of microorganisms by damaging their cell membranes during the water purification process [76,77].…”
Section: Introductionmentioning
confidence: 99%